Penggunaan Kapasitor Bank untuk Perbaikan Profil Tegangan Pada Penyulang Makariki Area Masohi - Muzakkir, Dita Arisandy; Haurissa, Marceau A F; Jamlaay, Marselin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
In the implementation of electric power distribution, various issues are frequently encountered. The distribution of electric energy through the distribution network often faces problems such as voltage drops. Power delivery through the distribution network to the load is prone to several challenges, particularly voltage drop. The Makariki feeder is classified as a relatively long radial feeder, with a total line length from the ULPL Masohi substation to the terminal point in Beben, Moti, measuring 63.37 km. Therefore, an analysis is needed to determine the voltage profile both before and after the use of a capacitor bank on the Makariki feeder distribution network. The longer the distribution line, the greater the voltage drop it experiences. The single-line diagram of the Makariki feeder was modeled in ETAP based on the obtained data. The simulation results showed that the voltage drop in the Makariki feeder under installed load conditions was 6.30%, under peak load conditions was 4.25%, and under off-peak load conditions was 3.25%. Based on these results, it can be seen that the voltage drop under installed load conditions exceeds the SPLN NO. 72 standard of 1987, which sets a maximum of 5%. After corrective measures using capacitor banks were applied to the installed load condition, voltage drops were reduced to 3.60% in scenario 1, 1.55% in scenario 2, and 2.85% in scenario 3. Among the three scenarios, all improvements showed a reduction in voltage drop on the Makariki feeder voltage profile under installed load conditions. However, the voltage drop percentages differed across scenarios. Scenario 2 demonstrated the most effective reduction in voltage drop among the three. Keywords: Voltage Profile, Capacitor Bank, Makariki Feeder, Etap Software